2021
DOI: 10.1111/ffe.13414
|View full text |Cite
|
Sign up to set email alerts
|

Influence of load interaction and hydrogen on fatigue crack growth behavior in steel pipelines under mean load pressure fluctuations

Abstract: Crack propagation in near neutral pH (NNpH) environment causes significant threat to pipeline integrity. Internal pressure fluctuations during pipeline operation create variable amplitude loading condition that can propagate corrosion fatigue cracks in NNpH environments. This study is aimed at understanding the effect of load interaction due to mean load pressure fluctuations on crack propagation in pipeline steel under NNpH conditions. The loading condition involved underload followed by an overload at set in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…A similar phenomenon was also observed in small-scale tests: no crack growth was detected in the specimen subjected to a monotonic loading even at the highest stress intensity factor used in the study [33]. It is therefore suggested in [34][35][36] that the growth of NNpHSCC cracks can be better characterized by corrosion fatigue (CF) than SCC. CF is one type of EAC that occurs under the synergistic effects of corrosion and cyclic stress [11,37].…”
Section: Nnphscc On Pipelinessupporting
confidence: 69%
See 1 more Smart Citation
“…A similar phenomenon was also observed in small-scale tests: no crack growth was detected in the specimen subjected to a monotonic loading even at the highest stress intensity factor used in the study [33]. It is therefore suggested in [34][35][36] that the growth of NNpHSCC cracks can be better characterized by corrosion fatigue (CF) than SCC. CF is one type of EAC that occurs under the synergistic effects of corrosion and cyclic stress [11,37].…”
Section: Nnphscc On Pipelinessupporting
confidence: 69%
“…Many researchers have claimed that cyclic stress is essential to the growth of NNpHSCC cracks [32][33][34][35][36]. Full-scale experiments showed that the absence of cyclic components in the loading spectra led to non-growth of NNpHSCC cracks in pipe specimens and that controlling pressure fluctuations in pipelines resulted in reduced crack growth [32].…”
Section: Nnphscc On Pipelinesmentioning
confidence: 99%
“…These cracks will converge with the main cracks to accelerate the corrosion FCP, so that the corrosion FCP can be completed at a lower number of cycles. 37 The corrosion FCP is strongly dependent on loading frequency. At a lower loading frequency, the longer the corrosion solution contacts the fresh metal at the crack tip in each cycle, the greater the corrosion damage.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…HE results in a loss of ductility, which is evident from the occurrence of brittle fracture features observed on the fractured surface. 15,18,19 Several viable mechanisms have been proposed to give insight into this phenomenon, including "hydrogen-enhanced local plasticity" (HELP), "hydrogen-enhanced decohesion" (HEDE), "hydrogenenhanced strain-induced vacancy" formation (HESIV), hydride formation, and "adsorption-induced dislocation emission" (AIDE). [20][21][22][23][24] Out of the proposed HE mechanisms, the HELP and HEDE models of HE mechanisms are mostly accepted.…”
Section: Introductionmentioning
confidence: 99%